PERAN KEJAKSAAN DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA PASCA UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Yasmirah Mandasari Saragih (Al-Adl : Jurnal Hukum, 2017)
AbstractThe criminal act of corruption in large numbers has the potential to harm the state's finances so as to disrupt development resources and endanger the political stability of a country. Currently corruption is transnational. The prosecutor's office as the case controller or Dominus Litis has a central position in law enforcement, since only the prosecutor's office can determine whether a case can be brought to the Court or not based on valid evidence as per criminal law. To carry out the task of eradicating corruption, the Attorney General can not work alone by relying on the ability of the prosecutor apparatus without cooperation with other agencies. According to the prevailing regulations, corruption investigators are prosecutors and police, so cooperation between the two law enforcers should be mutually supportive and mutually supportive for the successful investigation of criminal acts of corruption.Keywords: Prosecutor, Corruption, Eradication.